(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrity and Religious Liberty. Early Christian Claims of Religious Freedom and their applicability today Through this paper we aim to study the early methods successfully used by the first generations of Christians which earned their religious freedom during Constantin the Great, emperor of the Roman Empire. Due to the perseverance and courage of the believers, Christianity became, within a timespan of only three centuries, from a persecuted religious group, a tolerated religion, and shortly after ascended to the status of the official religion of the empire. This study will show that moral superiority, together with the moral benefits brought to the empire, played a decisive role in religious freedom recognition. Moreover, the unity and perseverance of the early Christians, along with the peaceful right claims which were granted by God through creation, provided ultimately religious liberty. Therefore, the present study intends to emphasize few of the methods used by the first Christian generations to promote their religious rights, and to find ways through which they can be successfully used today in order to consolidate religious rights worldwide.